Speech Disfluency Made by Male and Female Learners at Kampung Inggris Semarang - Abimanto, Dhanan; Hidayah, Yayuk; Halimah, Lili; Hasyim, Umar Al Faruq A (Anglophile Journal, 2021)
In utterance, there must be some disfluency whether in normal people or in stutterer. Moreover, the disfluency would be different if it was categorized into two based on the gender. The researchers’ figures out the disfluency based on the gender, male and female. The article was to find out any types of disfluency that appear on the male and female speeches, to find the dominant type of disfluency occured in male and female speeches, the difference between male and female speeches, and the factors causing the disfluency made by male and female speeches. The sample was 24 English learners at Kampung Inggris Semarang, 12 males and 12 females. In collecting the data the researchers used observation and interview. In analysing the data, the researchers used the theory from Clark and Wasow supported by Johnson and Bortfeld et.al. The result showed that nine types of disfluency occur in learners’ speech, i.e filler, silent pause, revision, incomplete phrase, broken word, repetition, grammatical disfluency, prolongation, and false start. The dominant disfluency occured in male and female speeches was filler. In the dominant disfluency, males produced more filers than females, whereas silent pause was more produced in female speeches. Besides, there was some factors causing disfluency made by male and female learners of Kampung Inggris Semarang, which were related to psychological factors. It included cognitive factors and affective factors. In total, male produced more disfluency than female. Besides that male learner made more factors which could affect the disfluency in their speeches than female learners, male learners were more likely not in mastering grammar and vocabularies and getting prepared in materials. Keywords: Speech Disfulency, Factors Speech Disfluency, Disfluency